Effect of Disclosure of Islamic Social Reporting, Cashless Society, and Company Size on Company Value (in Islamic Banks in ASEAN Period 2017-2023) - Dara Nitami; Ersi Sisdianto; Fatih Fuadi (Majapahit Journal of Islamic Finance and Management, 2025)
Company value is the main indicator in assessing the success of a company, which is measured by its stock price. The higher the company value, the greater the welfare of shareholders and the attractiveness to investors. This study aims to analyze the effect of Islamic Social Reporting (ISR), cashless society, and company size on company value in Islamic banks in ASEAN for the period 2017-2023. This study uses a quantitative method with secondary data obtained from the annual reports of Islamic banks. The research sample consisted of 12 Islamic banks operating in ASEAN consisting of Indonesia, Malaysia, Singapore, and Brunei Darussalam which were selected using the purposive sampling method for 7 years, so that the total observation was 84 samples. The data analysis technique used was panel data regression with the help of Eviews 10 software. The results of the study showed that partially, Islamic Social Reporting (ISR) had a significant effect on company value. Cashless society did not have a significant effect on company value and company size did not have a significant effect on company value. Simultaneously, Islamic Social Reporting (ISR), cashless society, and company size had a significant effect on company value. In Islamic economics, the value of a company is not only measured in terms of material, but also seen from the application of sharia principles such as justice, transparency and social responsibility. The limitations of this study lie in the limited sample coverage and the use of secondary data that relies on the availability of information in the company's annual report.